Monitoring of Main Outfall Drain and Southern Marsh in Iraq by Arithemitic Water Quality Index - Al-Janabi, Zahraa Zahraw; Maktoof, Afrah A.; Al-Ani, Rana R.; Al-Obaidy, Abdul-Hameed M. Jawad; TA., Mohammed M. (Iraqi Journal of Science, 2025)
This  study  set  out  to  assess  the  ecological  states  to  show  that  the  Main  Outfall  Drain  and  the  Southern  Marsh  are  viable  for  irrigation  use  and  the  preservation  of  aquatic  life.  Water  quality  conditions  at  four  sites  were  evaluated  using  the  weight  model.  Samples  were  taken  monthly  to  calculate  the  water  quality  index  (WQI)  for  two  seasons,  summer  of  2021  and  winter  of  2022.  Twenty-six  parameters  were  chosen  to  apply  the  WQI:  Cl-,  CO3-,  HCO32-,  Ca2+,  Mg2+,  pH,  electrical  conductivity  (EC),  NO3,  NO2,  NH3,  Na+,  K+,  dissolved  Oxygen  (DO),  water  temperature  (WT),  total  dissolved  solids  (TDS),  Mn,  Ni,  Pb,  Fe,  Cr,  Zn,  Cd,  Cu,  sodium  absorption  ratio  (SAR),  residual  sodium  carbonate  (RSC)  andsoluble  sodium  percent  (SSP).High  levels  of  Cl,  TDS,  Cu  and  Pb  were  found  in  all  sites  during  both  seasons,  and  their  concentrations  were  beyond  the  aquatic  life  protection  criterion.  Cl-,  Mg2+,  pH,  EC,  Na+,  Cu  and  Cd  were  above  the  permissible  limit  for  irrigation  uses.     The  results  of  the  index  for  protection  of  aquatic  life  and  irrigation  uses  ranged  between  72.12–372.47  and  131.24–158.1  respectively.  The  WQI's  ultimate  rating  ranged  from  very  poor  to  unfit  for  both  purposes.  Therefore,  only  tolerant  species  may  find  this  water  quality  acceptable  which  is  insufficient  to  support  the  presence  of  diverse  aquatic  life.